EARTH TIDE AND SEISMIC ACTIVITY IN THE VICINITY OF MOUNT EREBUS, ANTARCTICA - イケガミ, ヨシヒロ; オウチ, トル; カミヌマ, カツタダ; IKEGAMI, Yoshihiro; OUCHI, Toru; KAMINUMA, Katsutada (National Institute of Polar Research, 1989)
P(論文) The relation between temporal variation of earthquake frequencies and the earth tide in the vicinity of Mount Erebus, Antarctica was investigated. No significant correlation was found between the earth tide and seismic activity. Interestingly, remarkable periodicities of about 2-4 days and 10-20 days were found by the spectral analysis of this seismic activity. These may be explained as peculiar rhythms of the seismic activity. The effect of the earth tide on the seismic activity seems very small, as Mount Erebus is located at a very high latitude of about 80°S. This enabled us to observe an intrinsic nature of the seismic activity and to reveal these periodicities. departmental bulletin paper